PERCERAIAN DAN PERUBAHAN SOSIAL: SEBUAH TINJAUAN PERUBAHAN PERAN GENDER DALAM KONTEKS PERCERAIAN: - - -, Suci Rahmayani (LP2M Universitas Muslim Nusantara Al Washliyah, 2024)
Marriage is something that is central to human life, according to the 2019 law stipulates the age of marriage, namely 19 years for men and 19 years for women, marriage is inseparable from small problems which if left unchecked will escalate which can lead to divorce. , as is the case in Padangsidimpuan. Based on this, the purpose of this research is to find out how gender roles in the context of divorce have experienced social changes and cultural shifts, then to analyze how role changes after divorce affect children's welfare. The data analysis technique used in this research is data reduction, data presentation and conclusion. The results of the study show that one of the factors causing divorce is due to social changes in the form of changes in gender roles in husband and wife relationships. Divorce has an impact on children's welfare, namely children will feel uncomfortable living at home, experience behavioral disorders, get angry easily, and decrease children's performance at school due to lack of attention given by parents so that it hinders children's growth and development